1999
DOI: 10.1111/1467-6303.00016
|View full text |Cite
|
Sign up to set email alerts
|

A Regional Study Of Listed Companies' Compliance with International Accounting Standards

Abstract: The move towards international harmonisation of accounting standards has dominated the work programme of the Australian Accounting Standards Board in the past two years. Some have expressed concern that Australia is moving too quickly towards harmonisation when compared to other countries. This paper examines the extent of compliance with International Accounting Standards (IAS) in six countries in the Asia-Pacific region. By providing evidence as to the level of compliance with IAS in financial statements, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
2
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 11 publications
4
79
2
7
Order By: Relevance
“…This finding is consistent with Chalmers and Godfrey (2004), who also document a significantly positive relationship between size and FI disclosure. However, this result is inconsistent with a number of studies where the company size variable is insignificant (Glaum and Street, 2003;Hodgdon, 2004;Street and Bryant, 2000;Street and Gray, 2001;Tower et al, 1999). One possible explanation for the difference is that firm size is more heterogeneous among the current Jordanian sample than in other studies of developed countries.…”
Section: Insert Tables 4 and 5 Herecontrasting
confidence: 73%
“…This finding is consistent with Chalmers and Godfrey (2004), who also document a significantly positive relationship between size and FI disclosure. However, this result is inconsistent with a number of studies where the company size variable is insignificant (Glaum and Street, 2003;Hodgdon, 2004;Street and Bryant, 2000;Street and Gray, 2001;Tower et al, 1999). One possible explanation for the difference is that firm size is more heterogeneous among the current Jordanian sample than in other studies of developed countries.…”
Section: Insert Tables 4 and 5 Herecontrasting
confidence: 73%
“…Among these studies, a number have reported cases of significant non-compliance. Street and Gray (2000a,); Street and Bryant (2000); Tower, Hancock and Taplin (1999) ;Street, Gray and Bryant (1999);and Cairns (1999a) provided the initial evidence of significant non-compliance among companies purporting to use IAS. Street et al (1999) studied compliance with the ten IASs issued as part of the IASCs comparability project.…”
Section: Ifrss Compliancementioning
confidence: 99%
“…They stressed the importance of further training for accountants who are responsible for applying IAS in Kuwaiti companies to promote compliance. Tower et al (1999) undertook an empirical study of listed companies' compliance with IASs in Asia-Pacific countries. They measured compliance with IAS by extensive analysis of 1997 annual reports selected randomly from each of Australia, Hong Kong, Malaysia, Philippines, Singapore and Thailand.…”
Section: Ifrss Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…The most widely used variables were total assets (e.g., Wallace & Naser, 1996;Inchausti, 1997;Owusu-Ansah, 1998;Tower et al, 1999;Ho & Wong, 2001;Naser et al, 2002;Camfferman & Cooke, 2002;Abdul Hamid, 2004;Haniffa & Cooke, 2005;Ali et al, 2004;Barako et al, 2006;Othman et al, 2009;Khan, 2010;Galani et al, 2011), total sales (e.g., Wallace et al, 1994;Meek et al, 1995;Inchausti, 1997;Depoers, 2000;Naser et al, 2002;Prencipe, 2004;Rouf, 2011) and market capitalization (e.g., Naser et al, 2006;Ghazali, 2007;Chatterjee & Mir, 2008). Consistent with the findings of the majority of prior studies, it is, therefore, hypothesized that:…”
Section: Corporate Sizementioning
confidence: 99%